Misconceptions in the teaching of chemistry in secondary schools in Singapore & Malaysia - Chu, Chit Kay *; Hong, Koh Yiin * (Sunway University College, 2010)
Misconceptions are erroneous perceptions of what is universally accepted as physical laws that have been experimentally tested to date. There are many sources of misconceptions in the teaching of Chemistry and the origins of some of these misconceptions are discussed with reference to Malaysian and Singapore students. Surveys on students in the form of questionnaires, and Chemistry teachers having to conduct microteaching sessions with peer evaluations, have been shown to be effective tools in identifying some misconceptions among students and teachers. Many of these misconceptions are common with students of Chemistry world-wide arising mainly from text books and our general perceptions of things through multi media. Surveys in the form of questionnaires and micro-teach have been conducted to identify both students? and teachers? perceptions. Some of these misconceptions identified are derived from peers, family members within our different ethnicity and cultures. This is particularly important in this region of the world where there is so much diversity in language and culture. Malaysia, for example, has used English as the medium of instruction, reverted to Bahasa Malaysia and back again to English in the teaching of Science. This will invariably bring about a shift of conceptual visualization as we change from one language to another. The surveys also highlighted the importance of peer evaluation in an attempt to make teachers more aware of their misconceptions. The paper is by no means exhaustive and hopes to provide a general guideline for teachers of Chemistry in the region, to be aware of such misconceptions during their teaching of the subject.